Guggulsterone-releasing microspheres direct the differentiation of human induced pluripotent stem cells into neural phenotypes. (28th February 2018) - Agbay, Andrew; De La Vega, Laura; Nixon, Gillian; Willerth, Stephanie
Abstract: Parkinson's disease (PD), a common neurodegenerative disorder, results from the loss of motor function when dopaminergic neurons (DNs) in the brain selectively degenerate. While pluripotent stem cells (PSCs) show promise for generating replacement neurons, current protocols for generating terminally differentiated DNs require a complicated cocktail of factors. Recent work demonstrated that a naturally occurring steroid called guggulsterone effectively differentiated PSCs into DNs, simplifying this process. In this study, we encapsulated guggulsterone into novel poly-ε-caprolactone-based microspheres and characterized its release profile over 44 d in vitro, demonstrating we can control its release over time. These guggulsterone-releasing microspheres were also successfully incorporated in human induced pluripotent stem cell-derived cellular aggregates under feeder-free and xeno-free conditions and cultured for 20 d to determine their effect on differentiation. All cultures stained positive for the early neuronal marker TUJ1 and guggulsterone microsphere-incorporated aggregates did not adversely affect neurite length and branching. Guggulsterone microsphere incorporated aggregates exhibited the highest levels of TUJ1 expression as well as high Olig 2 expression, an inhibitor of the STAT3 astrogenesis pathway previously known as a target for guggulsterone in cancer treatment. Together, this study represents an important first step towards engineered neural tissues consisting of guggulsterone microspheres and PSCs for generating DNs that could eventually be evaluated in a pre-clinical model of PD.